Comparison between three times of heart rate measurement in horses - González, Daniela (2020)
The study aimed to determine possible differences between the measurement of heart rate for times less than 60 seconds (30 and 15 seconds) in horses. For this, 37 healthy adult horses were evaluated, and heart rate measurement was performed using a stethoscope and a stopwatch, simultaneously by three people. Heart rates were taken by 15” (t15) for person 1; 30” (t30) for person 2 and 60” (t60) for person 3. The mean and standard deviation of the three measurements were determined and compared by analysis of variance. Differences were found between t15 and t60 and between t30 and t60 (p<0.001); but with differences between 2 and 2.5 seconds between measurement times. In conclusion, taking the heart rate measurement in less than a minute could generate under or overvaluations.